CHARACTER EDUCATION BASED ON LOCAL WISDOM: EXPLORING THE "DONGKREK DANCE" CULTURE AS AN EFFORT TO INTERNALIZE CHARACTER VALUES IN LEARNING ARTS IN ELEMENTARY SCHOOLS - Umah, Restu Yulia Hidayatul (Al-Bidayah : Jurnal Pendidikan Dasar Islam, 2020)
Character education is considered the best solution to produce excellent students in character, personality and uphold the nation's noble values. Through local wisdom in each area, such as the Dongkrek dance culture, it is important to understand and improve character education in students. Therefore, it is necessary to explore more deeply character education based on local wisdom by exploring the Dongkrek dance culture to internalize character values in learning art in elementary schools. This study aims to describe the character education of Dongkrek dance and efforts to internalize it in learning arts in elementary schools. This research is qualitative research using descriptive analysis and a library research approach. Five main character educations are explored in the Dongkrek dance, including religion, cooperation, nationalism, independence, and integrity. Meanwhile, efforts to internalize it into art learning are by understanding the contents of the dance, performing, and developing the Dongkrek dance into a show.